A CROSS-SECTIONAL ASSESSMENT OF THE IMPACT OF LAND USE PRACTICES ON WATER QUALITY AND ECOSYSTEM HEALTH IN THE PALMIET RIVER, DURBAN, KWAZULU-NATAL. - Mbanjwa, Sibonelo Thanda (Student's Journal of Health Research Africa, 2025)
Introduction The Palmiet River in Durban, KwaZulu-Natal, is a vital watercourse that historically supported rich biodiversity and provided essential resources for domestic, agricultural, and industrial use. However, increasing pollution from anthropogenic land-use practices threatens its ecological integrity and socioeconomic value. This study aimed to assess the extent and impact of pollution on the water quality, biodiversity, and socio-economic sustainability of the Palmiet River. Methodology A cross-sectional mixed-methods approach was employed, combining quantitative and qualitative techniques. Water samples were collected from ten sites along the river and analysed for physicochemical (e.g., pH, dissolved oxygen, nitrates, phosphates, heavy metals) and biological (E. coli) parameters. GIS mapping was used to assess land use patterns, and semi-structured interviews were conducted with 20 stakeholders, including residents, municipal officials, and environmental practitioners. Results Statistical analysis revealed that water quality parameters in urban and industrial areas exceeded permissible limits. Nitrate concentrations ranged from 5.4 to 18.7 mg/L (mean: 12.1 mg/L), while phosphate levels averaged 4.3 mg/L, indicating eutrophication risk. Heavy metals such as lead and zinc were significantly elevated (p < 0.05) in industrial zones. Microbial contamination was severe near informal settlements, with E. coli counts exceeding 2000 CFU/100mL. Biodiversity assessments indicated a decline in sensitive macroinvertebrate taxa in polluted sites. Interview data underscored socio-economic consequences, including health concerns, restricted water use, and loss of livelihood for small-scale farmers. Conclusion Pollution from urban, industrial, and agricultural activities is severely impacting the ecological health and socio-economic functions of the Palmiet River. The dynamic influence of rainfall and land use exacerbates these effects. Recommendations Urgent interventions are needed, including stricter regulation of industrial discharges, promotion of sustainable farming practices, improved sanitation in informal settlements, effective stormwater management, and community-based river monitoring. These measures are critical for restoring ecosystem health and enhancing sustainable urban water governance.